Photo-triggered cargo release from liposome chlorin e6-bearing pullulan hybrid nanoparticles via membrane permeabilization. Issue 58 (12th November 2021) - Kawasaki, Riku; Ohdake, Reo; Eto, Takuro; Yamana, Keita; Nakaya, Toshimi; Ishida, Takenori; Kuroda, Akio; Ikeda, Atsushi
Abstract : A liposome chlorin e6-bearing pullulan nanogel hybrid was prepared as a light-triggered payload release platform. Abstract : A liposome chlorin e6-bearing pullulan nanogel hybrid was prepared as a light-triggered payload release platform. The current system enabled manipulation of the release profile of model drugs encapsulated by liposomes. Gelatin hydrogels that comprised hybrid nanoparticles could successfully control the delivery of cargo molecules to human mesenchymal stem cells with light stimuli without injury to the cells.